Evaluation of Scalability and Resilience of Hyperledger Fabric in Blockchain Implementation for Diploma Management - Pebriyanti, Cahyani; Suranegara, Galura Muhammad (Politeknik Negeri Batam, 2025)
This research aims to evaluate the performance of a Hyperledger Fabric-based blockchain system implemented for digital diploma management. The system is tested using the Caliper benchmark tool in various network and scalability scenarios, including normal conditions (baseline), network delay of 50ms, 100ms, 200ms, and 500ms; packet loss of 1%, 5%, 10%, and 15%; bandwidth limitation of 5 Mbps; high transaction load (scalability standard and scalability optimized); and extreme conditions in the form of Byzantine attacks with malicious nodes of 10%, 30%, and 50%. The evaluation was conducted using four key metrics: transaction success rate, failure rate, average transaction latency, and throughput (TPS). The system recorded high performance under normal network conditions with a success rate of 99.8%, latency of 0.89 seconds, and throughput of 9.7 TPS. Network disruptions such as delay, packet loss, and bandwidth limitation had only a minor impact, with the success rate remaining above 99% and latency gradually increasing. High load in the scalability scenario caused latency to increase to 27.21 seconds and failure rate to rise, but improved significantly after chaincode optimization. Meanwhile, the Byzantine scenario showed a drastic drop in performance with the success rate decreasing to 12.83% and the failure rate increasing to 87.17%. These results show that the Hyperledger Fabric-based digital diploma management system is resilient to common network disruptions and reliable at medium scale, but still requires strengthening the consensus mechanism to deal with extreme conditions and maintain reliability in environments that are not fully trusted.